Commercialization of Ruspolia nitidula (nsenene grasshoppers) in Central Uganda - Agea, J. G. Agea; Biryomumaisho, D.; Buyinza, M.; Nabanoga, G. N. (African Journals Online (AJOL), 2008)
Trade in Ruspolia nitidula commonly known as grasshopper and locally known, as Nsenene is becoming a valuable source of income for many poor people in central Uganda, which although modest in terms of monetary value, could nonetheless form a significant proportion of their annual income. Though eaten by a large proportion of the population in the central Uganda, there is much less documented information on its commercialization and income potential. A study was, therefore, conducted to document consumers' perceptions about eating these R. nitidula; marketing chain, market locations, and the people trading in R. nitidula; the average price, income generated and the challenges and opportunities for marketing it in central Uganda. Two divisions (Central and Kawempe) of Kampala City and one sub-county (Nyendo-Ssenyange) of Masaka district with high concentration of R. nitidula business were surveyed. Seventy R. nitidula traders and 70 consumers were interviewed. Data were edited, coded, entered and analyzed using Statistical Packake for Social Sciences (SPSS). Results show that R. nitidula is a delicacy and cultural food eaten by the majority of the people in central Uganda. The average retail price per kilogram of R. nitidula was Uganda shillings 5,000 (≈ US $2.80), which compares favourably with that of goat meat, which retails at approximately Uganda shillings 4,000 (≈ US $2.13) per kilogram in Kampala districts. The trade was dominated by men and characterized by wholesalers who buy R. nitidula from collectors and sell to retailers. The average price per kilogram of R. nitidula increases from collectors to wholesale traders and to retailers. Collectors charged the lowest price although their profit margins remained the highest. Several barriers, such as high market dues, hamper the trade in R. nitidula. There is a need to streamline the trade in R. nitidula so as to protect traders from high taxation by the market administrators. The possibility of adding value to the R. nitidula should be investigated because it is mainly being sold in fresh form and yet it has a short shelf life.